Duodenal Graft Perforation after Simultaneous Pancreas-Kidney Transplantation. (5th April 2017) - Sannomiya, Akihito; Nakajima, Ichiro; Ogawa, Yuichi; Kai, Kotaro; Koyama, Ichiro; Fuchinoue, Shohei
Abstract : A 45-year-old woman with type 1 diabetes and chronic renal failure on dialysis underwent simultaneous pancreas-kidney transplantation from a brain dead donor. On postoperative day 15, acute generalized peritonitis was diagnosed and emergency laparotomy was performed. Perforation of the donor duodenum was found, which had apparently resulted from duodenal compression by the tip of the intestinal fistula tube placed for decompression. The perforation was sutured and the intestinal fistula tube was exchanged. Following this, perforation repeatedly recurred at the same site and open repair at laparotomy was required a total of four times. The fourth operation involved both suturing the perforation and covering it with ileum, after which there was no further recurrence. The patient was discharged on posttransplantation day 219, with the pancreas and kidney grafts both functioning well. This report presents a rare complication of simultaneous pancreas-kidney transplantation.